The Effect Op Entrepreneurship Education Self-Confidence And Entrepreneurial Mindset Students’ Entrepreneurial Intention - Rahmadani, Atiqah; Soleh , Ahmad; E G , Ida Ayu Made (Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine the effect of entrepreneurship education, self-confidence and entrepreneurial mindset on entrepreneurial intentions of students of the Faculty of Economics, Dehasen University, Bengkulu. The method used is a quantitative method where data is obtained by distributing questionnaires to students of the Faculty of Economics and Business, totaling 83 respondents. The analysis method was processed using the SPSS version 25 program. The results of the analysis indicate that entrepreneurship education has no significant effect on entrepreneurial intentions. While self-confidence and entrepreneurial mindset have a significant effect on students' entrepreneurial intentions. With the results of multiple linear regression tests showing the equation Y = 0.857 -0.10 X1 + 0.497 X2 + 0.488 X3 + 1.805, the coefficient of determination (R square) value of SPSS Version 25 is 0.832 which means X1, X2, and X3 have an effect of 83.2% while the remaining 16.8% is influenced by other variables. The results of the t-test at a significance level of 0.05 explain that partially X1 does not have a significant effect on Y with a value of 0.941 > 0.05, X2 has a significant effect on Y with a value of 0.000 < 0.05 and X3 has a significant effect on Y with a value of 0.00 < 0.05. Based on the F test, X1, X2, and X3 have a simultaneous effect on Y with a result of 0.00 < 0.05.